Prevalence of dental anomalies in children in the central region of Cameroon - W. Kamgang; T. F. Kosyreva; N. S. Tuturov; O. V. Loginopulo; K. Abakeliya; I. Katbeh (LLC "Endo Press", 2022)
Aim.  To determine the occurrence of dentoalveolar anomalies and to determine the need for orthodontic care among the child population in the central region of Cameroon.Materials and methods. The study was conducted in 1008 children aged 3 to 15 years, including 511 girls and 497 boys. To assess the need for occlusal correction, the Index of Orthodontic Treatment Need (IOTN) was used, and the WHO international chart was filled out to assess the dental status. The use of the epidemiological index, based both on the aesthetic component of malocclusion and on objective clinical signs, made it possible to most reliably identify those in need of treatment.Results. As a result of the study, the average prevalence of dentoalveolar anomalies in children aged 3-15 years old, living in Yaounde, the capital of Cameroon, was 27.9%.Conclusion. The obtained data can be used for science-based planning of medical and preventive treatment.